Irrigant Agitation Techniques versus Passive Ultrasonic Irrigation for Removing Debris from Curved Root Canals: An Environmental Scanning Electron Microscopic Study - Pereira, Ã‰rika Cristina; da Silveira Bueno , Carlos Eduardo; Kato , Augusto Shoji; Fontana, Carlos Eduardo; Stringheta , Carolina Pessoa; Pelegrine , Rina AndrÃ©a (Iranian Endodontic Journal, 2021)
Introduction: The aim of this study was to compare the efficacy of passive ultrasonic irrigation (PUI) versus mechanical agitation of the irrigant promoted by the EasyClean (EC) and XP-Endo Finisher (XP-F) systems in removing debris from root canal walls, using environmental scanning electron microscopy (ESEM). Methods and Materials: Twelve curved mesiobuccal canals of mandibular molars were prepared with the ProTaper Next system up to file X2 (25/0.06). The specimens were embedded in flasks containing silicone putty, sectioned lengthwise, and a 4-mm long groove was made on the canal wall of the buccal half of the specimen, extending from 2 mm up to 6 mm short of the apex. Five cross-sectional markings were made along this groove to establish standardized locations for imaging. The same specimens were used to prepare a negative control group (without debris), a positive control group (completely covered by debris), and 3 experimental groups according to the final irrigation protocol employed: PUI, EC or XP-F. ESEM images were obtained and evaluated by 3 examiners. The amount of debris observed on the images was classified according to a 4-category scoring system. The kappa test was used to assess inter-examiner agreement, and the Kruskal-Wallis and Dunn tests were used to compare the scores (P<0.05). Results: The scores attributed to the PUI, EC, and XP-F groups were statistically similar to those attributed to the negative control group (P>0.05). Conclusion: Based on this in-vitro study, the mechanical agitation of the irrigant promoted by EC and XP-F was as effective as using PUI to remove debris from the root canal walls.